ANALISIS PENDISTRIBUSIAN ZAKAT FITRAH PERSPEKTIF IMAM SYAFI’I [Studi Di Desa Ciptasari KEC. Mesuji Raya KAB. Ogan Komering Ilir] - Nur Cahya Wibawanti Cahya; Wiwik Damayanti; Ambariyani (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2025)
The distribution of zakat fitrah in Ciptasari Village, Hamlet 5, Mesuji Raya District, OKI Regency is carried out every year before Eid al-Fitr. In the distribution of zakat, there is a discrepancy in the distribution of the amount of zakat which is only divided into 3 groups, namely the poor, amil and sabilillah, where the share of the poor is the least compared to the others even though the poor are the group that is most prioritized in the distribution of zakat. This type of research is field research and uses a qualitative approach method. The results of this study indicate that the practice of distributing zakat fitrah in Ciptasari Village, Hamlet 5 is not in accordance with the perspective of Imam Syafi'i where the distribution of fair and targeted zakat fitrah has not been achieved as stated in one of his books. The implication of this study is to highlight local zakat fitrah managers to be more selective and pay more attention to the conditions of the local community. Keywords: Distribution, Imam Syafi’I, Zakat al-fitr